Novel motivational interviewing‐based intervention improves engagement in physical activity and readiness to change among adolescents with chronic pain - Katalin Forgács‐Kristóf; Szilvia Ádám; Adrienn Vargay; János Major (Wiley, 2024)
Abstract Introduction Engaging adolescents with chronic pain in physical activities is challenging. Motivational interviewing (MI) combined with activity promotion may encourage teens to make behavioural changes. This research aimed to assess the feasibility and acceptability of our MI‐based physical activity promotion programme, the M3 training. Methods In our exploratory study with 35 adolescent-parent dyads, we evaluated the feasibility by enrolment, drop‐out and retention rates. Acceptability of the M3 training was examined by adherence rates and participation experiences through open‐ended questions. We also assessed changes in pain self‐efficacy and readiness to change after the M3 training intervention. Results The M3 training was feasible with an adequate enrolment (77.8%) and retention (85.7%) rate. Both teens and parents found the M3 training acceptable and considered exercise and physical activity the most helpful elements of the programme (36% and 37%, respectively). While self‐efficacy remained unchanged, we identified a significant increase in the readiness to change for adolescents and parents. Conclusion M3 training improved physical activity engagement while prioritising adolescents' autonomy. Furthermore, it appears to be a clinically relevant approach and could result in a positive shift in readiness to change within a shorter timeframe. Patient or Public Contribution The preliminary version of the M3 training was reviewed and commented upon by the public (adolescents and adults). Adolescents who participated in this study were designing their own movement programme, considering their lived experiences. Participants' feedback was used to create the online version of the M3 training (which will be published elsewhere).